2018
DOI: 10.1016/j.jid.2018.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Automated Dermatological Diagnosis: Hype or Reality?

Abstract: CONFLICT OF INTEREST WL is employed by SK Telecom. But the company did not have any role in the study design, data collection and analysis, decision to publish, or preparation of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 8 publications
0
82
0
1
Order By: Relevance
“…They found that the top-1 error rate was 71% and the top-5 error rate was 42%. Although the sample size of the images tested by Navarrete-Dechent et al [47] was small, these findings suggest that the sensitivity of the algorithm was significantly lower than had been presented in the original publication [31]. It is known that published algorithms may underperform in less than ideal conditions or when validated through external testing.…”
Section: Melanomamentioning
confidence: 88%
See 1 more Smart Citation
“…They found that the top-1 error rate was 71% and the top-5 error rate was 42%. Although the sample size of the images tested by Navarrete-Dechent et al [47] was small, these findings suggest that the sensitivity of the algorithm was significantly lower than had been presented in the original publication [31]. It is known that published algorithms may underperform in less than ideal conditions or when validated through external testing.…”
Section: Melanomamentioning
confidence: 88%
“…The algorithm published by Han et al [31] is one of the few that are publicly available and, consequently, Navarrete-Dechent et al were able to evaluate its generalizability [47]. These authors tested the algorithm with 100 biopsyproven, high-quality images from the International Skin Imaging Collaboration Archive; all 100 images were lesions from Caucasians in the USA.…”
Section: Melanomamentioning
confidence: 99%
“…For example, Navarrete-Dechent et al took Han et al's established an AI algorithm that was trained with a relatively diverse set of data and tested it in a unique database of Caucasian Americans from the southern United States. They found that the performance was suboptimal compared to how it was reported originally (88). The issue of generalizability is thus not simple to solve and may require either unique or extended data depending on the composition of the population being tested.…”
Section: Generalizabilitymentioning
confidence: 94%
“…Dermatologist collaboration has also been highlighted as essential (6). Systems need to be trained with the full spectrum of human populations and clinical presentations that challenge dermatologists in clinical practice (88). Systems can also benefit from receiving inputs on other metrics available to physicians such as anatomic location, duration of the lesion and images of unaffected skin (88).…”
Section: Next Stepsmentioning
confidence: 99%
“…The inclusion of metadata containing sociodemographic information about the patient (sex, skin type, race, and age) is thus necessary to verify the presence of biases related to imbalance or underrepresentation (Navarrete-Dechent et al, 2018). When possible, the obvious solution to this problem is to broaden the dataset by including images and data of patients from less represented groups.…”
Section: Limitations and Challengesmentioning
confidence: 99%